#### Answer

B=$\frac{2U-ET}{T}$

#### Work Step by Step

T=$\frac{2U}{B+E}$
(B+E)T=(B+E)$\frac{2U}{B+E}$
BT+ET=2U
BT=2U-ET
$\frac{BT}{T}$=$\frac{2U-ET}{T}$
B=$\frac{2U-ET}{T}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

B=$\frac{2U-ET}{T}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.